The Modeling of the North Equatorial Countercurrent in the Community Earth System Model and its Oceanic Component. (20th February 2019) - Sun, Zhikuo; Liu, Hailong; Lin, Pengfei; Tseng, Yu‐heng; Small, Justin; Bryan, Frank
Abstract: The North Equatorial Countercurrent (NECC) simulated by a coupled ocean‐atmosphere model and its oceanic component have been investigated and compared against oceanographic observations. Coupled model simulations using the Community Earth System Model version 2 are compared against ocean‐ice simulations forced by the second phase of the Coordinated Ocean‐ice Reference Experiments (CORE) data set. The modeled circulation biases behave differently to the west of and to the east of 120°W: the CORE‐forced ocean model largely underestimates the NECC transport to the west and the coupled model underestimates it to the east. Further analysis suggests that the surface wind stress and its curl is the most important forcing term for correctly simulating the NECC in both models. West of 120°W, the NECC biases in the ocean model are attributed to the southward movement of the maximum easterly trade winds in the Northern Hemisphere and the associated wind stress curl (WSC) pattern; east of 120°W, the NECC biases in the coupled model are attributed to the weak northward cross‐equatorial winds and southwestward gap winds, which lead to a weak WSC gradient at the latitude of NECC. Further analysis confirms that the WSC biases comes mainly from the zonal wind bias, which may in turn relate to the protocol of CORE‐II of adjusting reanalysis winds toward satellite data, which include the relative wind effect. Key Points: The NECC transport is underestimated in the POP west of 120°W and it is underestimated in the CESM east of 120°W West of 120°W, the POP's NECC bias comes from the southward movement of the easterly trade winds and WSC pattern in the northern hemisphere East of 120°W, the NECC biases in the CESM mainly attribute to the weak cross‐equatorial southerly winds and northeasterly gap winds